2021
DOI: 10.1017/s1047951121004583
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter versus surgical closure of atrial septal defects: a systematic review and meta-analysis of clinical outcomes

Abstract: Background: Atrial septal defects are a common form of CHD and dependent on the size and nature of atrial septal defects, closure may be warranted. The paper aims to compare outcomes of transcatheter versus surgical repair of atrial septal defects. Methods: A comprehensive electronic literature search was conducted. Primary studies were included if they compared both closure techniques. Primary outcomes included procedural success, mortality, and reintervention rate. Secondary outcomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…33 In subgroup analysis, our findings suggested that lung function and CPET test results are comparable among children with surgically closed ASD, transcatheter-closed ASD, and unrepaired ASD. Both surgical and percutaneous closure methods are effective interventions for ASD with similar mortality rates, and almost 85% to 90% of all secundum ASD can be closed by using a transcatheter approach, [34][35][36] although less evidence has directly compared catheter and surgical ASD closure in terms of CPET parameter. An observational study revealed a higher decreased VE/VCO 2 slope in ASD patients after catheter closure than surgical closure at 1-year follow-up, while echocardiographic parameters did not differ significantly.…”
Section: Discussionmentioning
confidence: 99%
“…33 In subgroup analysis, our findings suggested that lung function and CPET test results are comparable among children with surgically closed ASD, transcatheter-closed ASD, and unrepaired ASD. Both surgical and percutaneous closure methods are effective interventions for ASD with similar mortality rates, and almost 85% to 90% of all secundum ASD can be closed by using a transcatheter approach, [34][35][36] although less evidence has directly compared catheter and surgical ASD closure in terms of CPET parameter. An observational study revealed a higher decreased VE/VCO 2 slope in ASD patients after catheter closure than surgical closure at 1-year follow-up, while echocardiographic parameters did not differ significantly.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of percutaneously implanted occluding devices for the closure of OS ASD has become an increasingly popular alternative to surgical closure for patients with suitable anatomy, due to its minimally invasive nature and reduced rate of early complications and length of stay [ 2 , 3 ]. However, these devices can be associated with late complications, including residual shunt, device erosion, device migration, late device fracture, thrombus formation, infective endocarditis, and atrial arrhythmias [ 3 , 4 , 5 , 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are four types of ASD, and while all of them can be surgically closed, only the ostium secundum (OS) defect can be percutaneously closed. Thus, in recent years, the use of percutaneously implanted occluding devices for the closure of ASD has become an increasingly popular alternative to surgical closure for patients with suitable anatomy, due to its minimally invasive nature and reduced rate of early complications and length of stay [ 2 ]. However, these devices are associated with potential complications, both early and late [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Floroskopi ile ölçülen gerilmiş balon çapı ortanca değeri 14 mm (ÇAA 12.4-18)'di. Ortanca cihaz bel çapı 14 mm (ÇAA [13][14][15][16][17][18], ortanca cihaz sol atriyal (SlA) disk çapı 28 mm (ÇAA [26][27][28][29][30][31] ve SlA disk çapının toplam septal çapa oranı ortanca değeri %75 (ÇAA 68-81)'di. Ortanca floroskopi ve işlem süreleri sırasıyla 8 dakika (ÇAA 5.6-13.75) ve 36.5 dakika (ÇAA 30-49)'du.…”
Section: Study Populationunclassified